NM23 protein expression in colorectal carcinoma using TMA (tissue microarray): association with metastases and survival - Oliveira,Levindo Alves de (2010)
CONTEXT: NM23, a metastasis suppressor gene, may be associated with prognosis in patients with colorectal carcinoma. OBJECTIVE: To analyze NM23 expression and its association with the presence of lymph node and liver metastases and survival in patients operated on for colorectal carcinoma. METHODS: One hundred thirty patients operated on for colorectal carcinoma were investigated. Tissue microarray blocks containing neoplastic tissue and tumor-adjacent non-neoplastic mucosa were obtained and analyzed by immunohistochemical staining using a monoclonal anti-NM23 antibody. Immunohistochemical expression was assessed using a semiquantitative scoring method, counting the percentage of stained cells. The results were compared regarding morphological and histological characteristics of the colorectal carcinoma, presence of lymph node and liver metastases, tumor staging, and patient survival. Statistical analysis was performed using the Mann-Whitney test, the Kruskal-Wallis test and Fisher's exact test. Survival analysis was performed using the Kaplan-Meier method and the log-rank test. RESULTS: NM23 expression was higher in colorectal carcinoma tissue than in adjacent non-neoplastic mucosa (P<0.0001). NM23 protein expression did not correlate with degree of cell differentiation (P = 0.57), vascular invasion (P = 0.85), lymphatic invasion (P = 0.41), perineural infiltration (P = 0.46), staging (P = 0.19), lymph node metastases (P = 0.08), or liver metastases (P = 0.59). Disease-free survival showed significant association (P = 0.01) with the intensity of NM23 protein immunohistochemical expression in colorectal carcinoma tissue, whereas overall survival showed no association with NM23 protein expression (P = 0.13). CONCLUSIONS: NM23 protein expression was higher in neoplastic colorectal carcinoma tissue than in adjacent non-neoplastic mucosa, showing no correlation with morphological aspects, presence of lymph node or liver metastases, colorectal carcinoma staging, or overall survival. Disease-free survival was higher in patients with increased NM23 expression.